STRATEGI KEBIJAKAN PEMANFAATAN JASA LINGKUNGAN AIR SECARA BERKELANJUTAN DI TAMAN NASIONAL GUNUNG CIREMAI KUNINGAN-JAWA BARAT - Rismunandar Rismunandar (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2016)
Mount Ciremai National Park (TNGC) requires institutional policies for managing environmental services. This study aims to determine the sustainable management policy strategy for water environmental services, based on ecological, social and economical assessment. The approach used in this study is "multidimensional scaling" (MDS) through the analysis of RAP-JASLING AIR (Rapid Appraisal Sustainability Index for Jasling Air) to determine sustainable and performance of the management; and analysis of prospective to determine the policy strategy. The results shows that the ecological dimension index for TNGC in three areas, namely southern and central regions is quite sustainable and less sustainable for northern region. The economic dimension index for three regions seems to be less sustainable. The social dimension index for the three regions is quite sustainable. Intervention and improvements in attributes of each dimension needs to be implemented in order to reach sustainability in the future. On the other hand, prospective analysis resulted in four key factors that influence the policy of water environmental services in TNGC area and possibly to become alternative strategy for management policies, namely: management support for TNGC, income of community living in surrounding TNGC, efforts to improvecommunity's income, and protection of water springs.